PROBLEMS AND SOLUTIONS WHEN CREATING A DICTIONARY OF GRAMMATICAL TERMS (Scientific journal of the Fergana State University, 2024)
The article discusses the challenges and potential solutions in developing a comprehensive dictionary of grammatical terms. The research explores lexicology, new methodologies for dictionary creation, and the integration of modern digital tools. It suggests organizing grammatical terms thematically and creating a multilingual platform for presenting and translating common terminology.